Perception of Rural Community on the Effectiveness of Microfinance in Poverty Eradication Program - Darham, Suryani (2007)
Amanah Ikhtiar Malaysia (AIM) has distributed a total of RM 1.02 billion to 147,554 participants in rural areas under the microcredit program since it established in 1987. Following the footstep of Grameen Bank in Bangladesh, AIM is one of the NGOs, which plays an important role in lifting up the poor households out of poverty. AIM provided microcredit loan and non-financial assistance to the poor to increase their income through income generating activities. Thus, the objective of the study is to investigate the effectiveness of AIM microfinance as perceived by the recipients in eradicating poverty among rural poor. A sample of 1218 recipients that took loan from AIM in six states were selected as respondents to the study. In this study, purposive random sampling strategy was adopted. The surveys were conducted in the Northern Region, which consists of three states (Perlis, Kedah and Perak), two states in Eastern Region (Kelantan and Terengganu) and Sabah. After choosing these states, several towns in each states has been selected. The reason for choosing these states was due to its highest incidence of poverty in Malaysia meanwhile those towns were selected because the poverty incidence were high as well. Since AIM borrowers have a weekly meeting at a center, a random sample was drawn from AIM meeting centers in each town and identify the respondents who met the criteria for inclusion in this study. Descriptive analysis, chi-square analysis, factor analysis and logit model were applied to determine the effectiveness of AIM program as perceived by the borrowers in the eradication of poverty. The results showed majority of loan recipients agreed that AIM brought positive impacts on lives of the borrowers. On the other hand, there were significant relationships between demographic factors such as locations, level of education and years of experience as a member of AIM and level additional income generated by respondents. Factor analysis identified five factors that influence the success of AIM program from the recipients’ perceptions. These factors were as follows: community support, skills and knowledge development, decision making, income generating activity and improvement of well-being. This study explored various dimensions of respondents’ perceptions towards the effectiveness of microfinance of AIM in poverty eradication program. AIM activities are perceived by its recipients as effective and do contribute to poverty alleviation in Malaysia. AIM not only acts as an economic stimulator, but also far reaching social impacts on its members. This shows that microfinance institutions are a significant part of the infrastructure necessary for rural development.